STORYTELLING AND GAMES AS TOOLS OF TEACHING ENGLISH - Nilufar Aliboyeva (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores the role of storytelling and games as effective teaching techniques in modern education. It highlights how these methods enhance student engagement, support the development of cognitive and emotional skills, and promote interactive, learner-centered instruction. The article also addresses the importance of aligning these tools with educational goals to ensure meaningful learning outcomes.